How Can Imaging Help the Radiation Oncologist in Multiple Myeloma Treatment - Liliana Belgioia; Stefano Vagge; Alberto Tagliafico; Renzo Corvò (Medicina, 2020)
Multiple myeloma is an incurable malignant tumor of plasma cells of the bone marrow; most patients present a disseminated disease with important bone involvement. Even though a chemotherapy-based approach is the major treatment, radiotherapy often has a supportive role for symptom relief but also a radical role for patients with indolent disease or localized forms. In both cases imaging is the basis for treatment planning and for correct patient classification. This paper aims to describe and summarize how radiation oncologists could use imaging information to personalize the treatment for each patient.